The key to everything - Schmatz, Pat (Somerville, Massachusetts : Candlewick Press, 2018)
Returning from camp, eleven-year-old Tash is dismayed to find that her elderly next-door neighbor has disappeared and is compelled to use the key that may possess magic.
Keywords: Camps -- Fiction; Magic -- Fiction; Neighbors -- Fiction; Family life -- Fiction; Camps -- Fiction; Magic -- Fiction; Neighborhood -- Fiction; Family life -- Fiction